Migrants, television and Australian stories - Darian-Smith, Kate, author. Link Link
1 online resource (310 pages)
Keywords: This book examines the intertwined histories of television and migration in Australia, told from the perspectives of migrants who worked in the screen industry and the many more who watched television. Their stories demonstrate how Australia's growing cultural diversity has challenged conventional representations of 'Australianness' on television, and how ongoing advocacy has supported the growing inclusivity of multiple narratives and diverse experiences on screen.Migrants from many backgrounds were instrumental in the establishment in 1956 of Australian television, working behind and in front of the cameras as producers, directors, writers, technicians and actors. From early broadcasting to the digital present, portrayals of cultural differences have often been shaped by appropriation, ethnic stereotyping and racism. This has occurred across a range of formats from drama to comedy to news and reality shows. Many in the industry have responded with resilience and creative adaptation, as they have increasingly taken control of the ways that migrant stories are told and diversity is celebrated.The first comprehensive Australian study of migrants and television, this book considers the ways multicultural audiences have experienced the small screen over seven decades. Drawing on rich oral histories, it analyses the memories of television in the work, school, family life and leisure of migrant communities and their broader engagements with Australian culture. Research in the archives of broadcasters and production companies reveals how non-Anglo Australian characters were constructed, and how such portrayals have shifted. This new history takes us to digital screen production and consumption today, exploring how Australians of many diasporas engage with the global network of screen content in the twenty-first century. It is essential reading for media professionals, advocates, students and those interested in the intersections between media, cultural diversity and the nation.